ANALISIS KESETARAAN HAK DAN KEWAJIBAN SUAMI-ISTRI PERSPEKTIF MUSDAH MULIA DALAM KONSEP PEMBAHARUAN KELUARGA ISLAM DI INDONESIA - Zulfa Insiyah (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2018)
Islam does not recognize gender discrimination between men and women. The presence of Islam among humankind is intended to elevate the status of the mustadh‘afīn (the marginalized), such as the poor, slaves, and women who experience discrimination in the fulfillment of their rights. Although Islam teaches equality to its followers, in reality there are still widespread practices of marginalization, discrimination, and oppression against these vulnerable groups, particularly women. Ironically, many of the cases experienced by women originate within the family itself. It appears that state legislation, especially in the field of family law, is considered insufficient and ineffective in providing firm protection against the oppression of women. Consequently, feminists such as Musdah Mulia have spoken out to challenge the marginalization and injustice faced by women in the fulfillment of their rights. Women continue to be positioned as secondary beings after men, while men tend to perceive themselves as superior. Since family law (more specifically, the Compilation of Islamic Law/KHI) is suspected of being unable to adequately address these issues, Musdah Mulia and the Working Group Team formulated reforms in the field of family law in order to restore the rights and obligations of men and women to their proper and equal positions.